Ethical Quandaries in The BBC Audio-Visual Documentation of Sexual Harassment in West African Universities - Azeez, Abolaji (The Journal of Society and Media, 2025)
In the universities, there has been limited attention on how victims secure evidence to challenge sexual harassment. The study explored the documentation and ethics of audio-visual evidence of sexual harassment in Nigerian and Ghanaian universities. Through a qualitative approach, the BBC Sex4Grade video and Nairaland discourse of sexual harassment in public domain were purposively selected. The data were subjected to content analyses using ethical quandaries. The need for evidence birthed the premediated documentations through institutional and informal supports. The use of smart cameras without the consent of the male lecturers heralded ethical questioning. Interpretation of gestures were subjective while all scenarios shared alternative meanings. The visual clips revealed disparities and contextual negotiation in social construction of sexual harassment between female students and their suspected lecturers The evidence did not satisfy all ethical conditions, yet the visual evidence remained the last resort to justice since legal framework was weakened by patriarchal system. However, Thus, the installation of CCTV at workplace with transparency with informed consent of the employees would prevent sexual harassment which strengthen legal framework and female’s proactiveness in seeking legal redress with acceptable ethical milieu.